2021
DOI: 10.3390/ijerph18073648
|View full text |Cite
|
Sign up to set email alerts
|

Determining Factors in the Use of Urban Parks That Influence the Practice of Physical Activity in Children: A Systematic Review

Abstract: The design and/or remodelling of urban parks is a good health strategy to alleviate the lack of physical activity (PA) in children and, consequently, the different health problems derived from this. The main objective of the present study was to obtain a systematic review of the design features and characteristics that influence users’ visits to urban parks and the PA engagement in them. A literature search was carried out in the Web of Science (WOS) and Scopus databases during the months of June and July 2020… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 104 publications
1
10
0
3
Order By: Relevance
“…The study found that the layout of GOS was obviously related to the spatial distribution of children's PA. Children often stayed and played around the sports field, playground, squares, and grassland with cover, according to their location records. The findings aligned with previous studies showing that these areas were the most attractive part of GOS ( 56 , 57 ). The areas with recreational facilities and natural features could always facilitate more outdoor play for children because they provided abundant attractive places to promote enthusiastic and diverse activities.…”
Section: Discussionsupporting
confidence: 91%
“…The study found that the layout of GOS was obviously related to the spatial distribution of children's PA. Children often stayed and played around the sports field, playground, squares, and grassland with cover, according to their location records. The findings aligned with previous studies showing that these areas were the most attractive part of GOS ( 56 , 57 ). The areas with recreational facilities and natural features could always facilitate more outdoor play for children because they provided abundant attractive places to promote enthusiastic and diverse activities.…”
Section: Discussionsupporting
confidence: 91%
“…A study with 6 to 11 (n = 724) year old children reported that children whose parents perceived their neighborhood as safe for walking and cycling were more likely to use public recreation facilities such as parks and playgrounds [10]. Furthermore, parents' satisfaction with quality and park design was also associated with park usage [44][45][46]. According to a systematic review of the literature, factors that may encourage park and playground usage include being close to home, providing a space that supports sport, playground equipment, and being safe and clean [44].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, parents' satisfaction with quality and park design was also associated with park usage [44][45][46]. According to a systematic review of the literature, factors that may encourage park and playground usage include being close to home, providing a space that supports sport, playground equipment, and being safe and clean [44]. Moreover, many studies have supported the hypothesis that children who more frequently use parks/playgrounds have a lower BMI, less screen time, and greater overall physical activity [10,11,13,[47][48][49][50].…”
Section: Discussionmentioning
confidence: 99%
“…Neben finanziellen Unterstützungen in (besonders) bedürftigen Familien ist die Förderung eines gesunden Lebensstils durch eine entsprechende Gestaltung von Lebenswelten und Bewegungsräumen mit Parkanlagen, Grünflächen, Spielplätzen et cetera im Sinne einer gesteigerten Moveability sinnvoll (Padial-Ruz et al. 2021 ). Auch wenn verhältnispräventive Interventionen am ehesten erfolgversprechend sind, werden Maßnahmen im Bereich der öffentlichen Gesundheit oft unzureichend finanziert.…”
Section: Diskussion Und Fazitunclassified